Pediatric Intensive Care Provider Attitudes About Children with Medical Complexity and Neurologic Impairment: A Qualitative Study - Elizabeth J. Bleed; Leonardo Barrera; Mickayla Jones; Seema K. Shah; Megan Crowley-Matoka; Carolyn C. Foster (Children)
(1) Background: Children with medical complexity (CMC) and neurologic impairment (NI) are a growing population in pediatric intensive care units (PICUs). (2) Objective: Our aim was to explore and describe the experiences and beliefs of PICU providers caring for CMC with NI. (3) Methods: A qualitative interview-based study was conducted. Participants were 20 providers (12 attendings and 8 nurse practitioners) who met inclusion criteria of being a faculty, fellow, or advanced practice provider who worked in a PICU; residents were excluded. Participants were recruited via purposive and snowball sampling until information power was reached, and came from seven PICUs across six states, with 10 participants from the authors’ home institution and 10 from external PICUs. Data were collected via recorded videoconference interviews, which were transcribed. Analysis was conducted and relevant themes were identified using the analytic technique of thematic analysis. Rigor was assured by using two coders. (4) Results: Four main themes were identified: (i) providers view CMC with NI as a distinct population of growing importance; (ii) CMC with NI have care needs that challenge traditional perceptions of PICU practice; (iii) PICU providers expressed ambivalence towards caring for CMC with NI; and (iv) some PICU providers have developed adaptive strategies. (5) Conclusions: This population challenges the typical notion of what pediatric critical care represents. Providers display ambivalence about caring for these patients but can develop strategies to make this work meaningful. Understanding PICU clinicians’ views about CMC with NI can provide insights for improved patient care and reduced provider burnout as the field adapts to this population.